Vessel wall stiffness in ankylosing spondylitis patients taking nonsteroidal anti-inflammatory drugs - I. Z. Gaidukova; A. P. Rebrov; E. V. Khondkaryan; A. V. Aparkina (Современная ревматология)
Changes in vessel wall stiffness are a sign of endothelial dysfunction and vascular remodeling at reversible, preclinical stages and may be a marker for cardiovascular disease, including in the use of nonsteroidal anti-inflammatory drugs (NSAIDs).Objective: to study changes in vessel wall stiffness indicators in patients with active ankylosing spondylitis (AS) without cardiovascular diseases during short- and long-term therapy with NSAIDS.Patients and methods. The investigation enrolled 164 AS patients aged older than 18 years. Of them 60 patients took amtolmetin guacil (AMG) daily for 3 months within the framework of the CORONA trial, the other 104 patients received nimesulide at least thrice weekly for 60 months (the index of NSAID use was 56%) within the framework of the PROGRESS study. Vessel wall stiffness indicators (augmentation indices and aortic pulse wave velocity (PWVao)) were studied in all the patients at baseline and after 3 (for those who took AMG) and 60 (for those who received nimesulde) months.Results. At baseline, AS activity and cardiovascular risk factors were comparable in the short- and long-term follow-up groups. The mean values of aortic augmentation index (AixAo) in the patients taking AMG were 13.5% [6.08; 22.08] at baseline and 14.25% [9.4; 24.25] after 3 months of therapy (p=0.18); PWVao was 7.7 [6.72; 9.41] and 8.46 [7.28; 9.96] m/sec, respectively (p=0.007). At the same time, PWVao was >10 m/sec only in 6 (10%) patients at baseline and in 12 (20%) following 3 months. In the group of patients taking NSAIDs long, AixAo was 21.5% [11.08; 34.25] at baseline and 18.25% [09.33; 26.28] at week 12 (p=0.3); PWVao was as high as 7.6 [6.56; 7.91] at baseline and 7.8 [7.22; 8.1] m/sec at week 12 (p=0.12). The PWVao of >10 m/sec was found in 20 (19.2%) patients at baseline and in 22 (21.15%) after 60 months of follow-up and treatment. The number of patients with unidirectional changes in vessel wall stiffness indicators did not differ in the 3- and 60-month use of NSAIDs. Conclusion. During 3-month NSAID therapy, the patients with AS showed a slight increase in PWVao in the absence of changes in the other indicators of vessel wall stiffness. At the same time, the mean values of PWVao remained within the normal range and its increase >10 m/sec was detected only in 20% of the patients. Long-term NSAID therapy in AS patients without cardiovascular diseases was unaccompanied by a change in the values of vessel wall stiffness and PWVao.